An intraday dispatch strategy for demand-side flexible resources based on two-stage optimization - Wang, Liqiang; Liu, Hongqing; Wang, Qi; Cao, Bin; Cong, Yu; Ding, Yujin; Zheng, Xiuxian (Frontiers in Energy Research, 2024)
Demand-side flexible resources, represented by air conditioners and electric vehicles, can participate in grid dispatch, improving the economic and reliability of system operation. To this end, this paper proposes an intraday dispatch strategy for demand-side flexible resources based on two-stage optimization. First, based on a generalized energy storage model, the adjustable flexibility of demandside flexible resources is modeled. Second, to hinder the uncertainties related with markets and demand-side flexible resources, the rolling optimization is adopted for the optimal bidding, thus enabling demand-side flexible resources to participate in the intraday market with low risks of profit losses. Third, based on the bidding decision, real-time dispatch optimization is carried out to cope with the system operation deviation caused by forecast errors. Then, in the real-time control stage, the dispatch instructions are decomposed to the control units to achieve power tracking. Finally, the proposed method is simulated and verified on a test system. The results show that by coordinating the operation of demand-side flexible resources through two-stage optimization, the uncertainties of renewable energy output, market price, etc. can be effectively overcome, and the economics of system operation can be improved.